ChemInform Abstract: Preparation of Spiro[4.4]oxaphospholene and ‐azaphospholene Systems from Carbohydrate Templates. Issue 10 (11th March 2014) - Moura, Marina; Josse, Solen; Postel, Denis
Abstract Some new title compounds such as (IV), (VI), (VIII), and (XI) are prepared in order to test their biological activity.